Factors influencing treatment recommendations for base of 5th metatarsal fractures in orthopaedic residency programs. Issue 4 (June 2020) - Chan, Jimmy J.; Mohamadi, Amin; Kaiser, Philip; Stupay, Kristen; DiGiovanni, Christopher; Kaplan, Jonathan R.; Cerrato, Rebecca; Jeng, Clifford; Vulcano, Ettore
Highlights: A prospective study with survey focusing on treatment recommendations for 5th metatarsal fractures among 72 residents in two ACGME-accredited residency program. Overall concordance rate was 44% between residents and fellowship-trained foot and ankle surgeons. There was no increase in agreement rate with increase PGY-level. Only slight inter-observer agreement among all residents. Abstract: Background: Management of proximal 5th metatarsal fractures remains a controversial topic in orthopaedic surgery. Both operative and non-operative approaches have been described in the clinical setting. This confusion has led to non-standardized treatment recommendations for proximal 5th metatarsal fractures. This study was designed to analyze concordance rate of treatment recommendations between orthopaedic trainees and orthopaedic foot and ankle experts. Methods: An online survey containing 14 cases of proximal 5th metatarsal fractures were distributed to 92 orthopaedic residents in two ACGME-accredited programs. Relevant weight-bearing radiographs, patient's age and gender were provided, and two questions regarding treatment recommendations were surveyed. Resident's recommended treatment was then matched against ultimate treatment by orthopaedic foot and ankle experts. ANOVA and T-test are used for associations between the rate of concordant treatment with PGY and trainee foot and ankle experience. Fleiss' kappa was used to assess the inter-observer agreement. Results: Seventy-two residents returned the survey. The overall concordance rate was 43.98% with no correlation between agreement rate and PGY-years. No difference in agreement rate was observed between residents who had completed their foot and ankle rotation versus those who had not. There was a slight inter-observer agreement in recommending treatment among all residents (κ = 0.117, 95% CI: 0.071–0.184). Conclusions: Our data demonstrated no significant concordance between resident level in training regarding proximal 5th metatarsal fracture treatment decisions, nor between residents and subspecialty-trained foot and ankle surgeons. Increased rotations with foot and ankle fellowship-trained surgeons throughout residency may be desirable to improve the quality of residency training. Level of Evidence: III.